2015
DOI: 10.5194/cpd-11-5509-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Climatic and insolation control on the high-resolution total air content in the NGRIP ice core

Abstract: Abstract. Because the total air content (TAC) of polar ice is directly affected by the atmospheric pressure, its record in polar ice cores was considered as a proxy for past ice sheet elevation changes. However the Antarctic ice core TAC record is known to also contain an insolation signature, although the underlying physical mechanisms are still a matter of debate. Here we present a high-resolution TAC record over the whole North Greenland Ice Core Project ice core, covering the last 120 000 years, which inde… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…This correlation indicates that the bubble air was squeezed out before close-off, resulting in smaller air contents when overloading pressure was higher, eventually inducing higher pressure in the bubbles and thus enhanced δAr/N 2 depletions. This observation is also consistent with recent findings that abrupt increases of accumulation rate at abrupt warming during the last glacial period induced reductions in air contents (Eicher et al, 2015). In addition, artificial sintering of snow with higher pressure has been shown to contain much smaller air content than ice cores, owing to the lack of time to develop spherical cavities by vapor transport (B. Stauffer, personal communication, 2015).…”
Section: Total Air In Bubblessupporting
confidence: 80%
“…This correlation indicates that the bubble air was squeezed out before close-off, resulting in smaller air contents when overloading pressure was higher, eventually inducing higher pressure in the bubbles and thus enhanced δAr/N 2 depletions. This observation is also consistent with recent findings that abrupt increases of accumulation rate at abrupt warming during the last glacial period induced reductions in air contents (Eicher et al, 2015). In addition, artificial sintering of snow with higher pressure has been shown to contain much smaller air content than ice cores, owing to the lack of time to develop spherical cavities by vapor transport (B. Stauffer, personal communication, 2015).…”
Section: Total Air In Bubblessupporting
confidence: 80%
“…Reversing the approach, one can calculate atmospheric pressure during gas trapping from temperature (δ 18 O ice ), the empirical relationship between close-off volume and temperature, and the ideal gas law. In addition, Raynaud et al (7) and others (26,27) identified a link between total air content and local summertime insolation. Accounting for this link, NEEM et al (6) quantified the effect of insolation and estimated that, during the Eemian, elevation at NEEM was within a few hundred meters of the present elevation.…”
mentioning
confidence: 98%
“…Freitag, personal communication, 2016) but also by daily weather events. Hutterli et al (2009) state that the total temperature gradient metamorphism (tTGM) influences the physical properties of the snowpack. tTGM is not necessarily synchronous with insolation, leading to a lag between the orbital parameters and the proxies depending on snow structure.…”
Section: Introductionmentioning
confidence: 99%